Alawi-Sunni Dichotomy with Respect to The Intercultural Communication: The Case of Tunceli and Elazığ - Yağbasan, Mustafa; Öztürk, Ali (Muş Alparslan Üniversitesi, 2016)
The geography of the Anatolia presents a rich appearance with its multicultural structure. Turkish and Kurdish cultures are ethnically and Alawi and Sunni beliefs are theologically dominant and draw attention with their dominant status in Turkey.  There is no doubt that Alawi and Sunni societies have communicated and interacted with each other in various areas from the past to the present.  When political contemplations are put aside, it is possible to say that the discrepancy and the lack of communication between the mentioned cultures stay at the marginal dimension mostly based on   prejudices. The main purpose of this study is to put forward what the extent of communication of the Turkish and Alevi societies having different belief cultures in Turkey is. The study is of great importance in terms of studying how the mentioned cultures realize each other, at what level the links and the neighbor relations are, and what they think about the differences and the similarities between the traditions. Tunceli and Elazığ cities in Turkey have been selected as samples in order to obtain objective data. The obtained data have been analyzed with SPSS program and have been tried to comment on. In conclusion, significant findings about the communication, interaction and realisation between the Alawi and Sunni beliefs have been obtained.

Anadolu coğrafyası çok kültürlü yapısıyla zengin bir görünüm arz etmektedir. Türkiye’de etnik anlamda Türk ve Kürt kültürleri, teolojik anlamda ise Alevi ve Sünni inanışları baskın ve başat konumları ile dikkat çekmektedir. Alevi ve Sünni toplumları şüphesiz geçmişten günümüze dek farklı alanlarda birbirleriyle iletişim ve etkileşim içerisinde olmuşlardır. Siyasi mülahazalar bir tarafa bırakıldığında adı geçen kültürlerarasındaki uyuşmazlık ve iletişimsizliklerin daha ziyade önyargılara dayalı olarak marjinal boyutta kaldığını söylemek mümkün görünmektedir. Bu çalışmanın temel amacı, Türkiye’de farklı inanç kültürüne sahip olan Alevi ve Sünni toplumların birbirleriyle olan iletişimlerinin hangi boyutta olduğunu ortaya koymaktır. Araştırmanın bahsi geçen inanç kültürlerinin birbirlerini nasıl algıladıklarını, kurdukları bağların ve komşuluk ilişkilerinin hangi düzeyde olduğunu, gelenekler arasındaki farklılıklara veya benzerliklere nasıl baktıklarını incelemesi açısından önem arz etmektedir. Nesnel verilere ulaşmak amacıyla bu araştırmada Türkiye evreninden hareketle Tunceli ve Elazığ illeri örneklem olarak seçilmiştir. Veriler SPSS programında analiz edilmiş ve yorumlanmaya çalışılmıştır. Araştırma sonucunda Alevi ve Sünni inançları arasındaki iletişime, etkileşime ve algıya yönelik önemli bulgulara ulaşılmıştır.
Kültürlerarası İletişim Bağlamında Alevi-Sünni Dikotomisi: Tunceli ve Elazığ Örneği